Supplemental L-arginine improves feed conversion and modulates lipid metabolism in male and female broilers from 29 to 42 days of age - Filho, S. T. S.; Lima, E. M. da C.; Oliveira, D. H. de; Abreu, M. L. T. de; Rosa, P.; Laurentiz, A. C. de [UNESP]; Naves, L. de P.; Rodrigues, P. B. (Elsevier B.V., 2021)
The excessive accumulation of abdominal fat in broilers is an economic waste. Supplemental dietary L-arginine has been shown to reduce lipogenesis in broilers, but studies on this subject are still scarce. Two experiments were conducted in a 5 x 2 factorial design, with five L-arginine concentrations in diets (0, 3, 6,9 and 12 g/kg) provided to male and female broilers, from 29 to 42 days of age, reared in boxes or cages, with six replicates of 23 broilers per box and six replicates of three broilers per cage. totalling 1560 broilers. Data on performance, carcass and cuts yield, abdominal fat deposition, chemical composition of the breast, lipid profile and liver enzyme activity were evaluated in experiment 1. In experiment 2, the balance and retention of nitrogen, metabolizability coefficients and metabolizable energy of feed were determined and the treatments were evaluated in six replicates of three broilers per cage, totalling 180 broilers. In both experiments, there was no interaction (P> 0.05) between L-arginine concentration in the diet and sex of the broilers for all parameters evaluated. Male broilers showed higher (P < 0.05) weight gain, noble cuts yield, levels of CP and mineral matter in the breast, better feed conversion (P <0.05) and lower (P <0.05) malic enzyme activity in the liver and abdominal fat deposition. On the other hand, regardless of sex, the increase in L-arginine concentration in the diet improved (P < 0.05) the feed conversion in addition to reducing (P < 0.05) serum levels of total cholesterol and low-density lipoprotein cholesterol, the malic enzyme activity in the liver and abdominal fat deposition. In conclusion, male broilers had better productive results than females. However, supplementing the diet of male or female broilers from 29 to 42 days of age with L-arginine at a concentration of 6.87 g/kg represents a nutritional strategy to improve feed conversion and reduce circulating triacylglycerol and cholesterol levels. NADPH synthesis by liver malic enzyme and abdominal fat deposition, without negatively affecting the carcass and noble cuts yield, the amount of nitrogen excreted by the broilers and the energy value of the feed. (C) 2020 The Authors. Published by Elsevier Inc. on behalf of The Animal Consortium.
Keywords: Abdominal fat; Lipidogram; Lipogenesis; Malic enzyme; Performance